An experimental study of combustion, performance, exergy and emission characteristics of a CI engine fueled by Diesel-ethanol-biodiesel blends. (15th December 2017) - Paul, Abhishek; Panua, Rajsekhar; Debroy, Durbadal
Abstract: The present work is an attempt to conduct a complete analysis of a CI engine subjected to a number of blends of Diesel-ethanol and Pongamia piñata methyl ester (PPME). In this study, the PPME percentage is fixed at 50% and ethanol percentage is increased from 5% to 20% with intervals of 5%, thus reducing the diesel participation. A comprehensive analysis of performance, exergy, combustion and emission characteristics was carried out, which lead to a conclusion that the D35E15B50 blend with 15% ethanol showed best engine performance characteristics with 21.17% increase in brake thermal efficiency and 4.61% decrease in BSEC at full load. The combustion analysis also revealed increase in cylinder pressure and heat release rate indicating improvement in combustion condition for the above-mentioned blend. The D35E15B50 blend also showed a substantial improvement in unburned hydrocarbon and carbon monoxide emissions but it was penalized with a marginal increase in NOx emission. The exergy analysis showed a 25.64% increase in exergetic efficiency and 22.02% decrease in exergy destruction rate and 21.06% decrease in entropy generation rate at full load condition for D35E15B50 blend. The tradeoff study involving BSEC, NOx emission and sustainability index indicated a higher sustainability prospect for the D35E15B50. Highlights: Exergy analysis of an existing diesel engine fueled with various Diesel-Ethanol-Biodiesel blends. Optimal performance, emission & exergy characteristics achieved with Diesel-Ethanol-Biodiesel blend with 15% ethanol. Possible frame work for a sustainable use of ethanol in a CI engine.